NeoEduc: A Synchronous AI-Driven 3D Avatar Tutor for Middle-School Robotics - Sebastião, José A.; Figueiredo, Lucas S. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Traditional education, particularly in hands-on subjects like robotics, often struggles to provide personalized, real-time student support due to teacher time constraints and students’ reluctance to seek help in a public setting. This paper introduces NeoEduc, an AI-driven tutoring platform that presents a 3D avatar for conversational guidance in a virtual robotics lab, allowing middle-school students to interact via voice or text and receive adaptive feedback tailored to their performance history. The solution integrates an adaptive large language model (LLM) back-end to offer scalable, engaging, and private pedagogical support. We evaluated the platform with middle school students (N 20) in a robotics learning environment, using standard usability and user experience questionnaires (SUS, UEQ-S, NPS), as well as qualitative analysis of interviews and observations. The results demonstrate high usability (mean SUS score of 78.0) and user satisfaction (NPS of +75). Qualitative findings revealed increases in student engagement and autonomy, a potential reduction in teacher workload, and a notable acceleration of task completion, particularly in a comparative experiment where the NeoEduc groups significantly outperformed the control groups. NeoEduc presents a framework for creating educational experiences that leverage AI and virtual environments. The system’s ability to be configured by teachers towards ethical and pedagogically aligned posture highlights its potential to scale adaptive and immersive learning while mitigating social pressures in the classroom.